Early and progressive impairment of spinal blood flow–glucose metabolism coupling in motor neuron degeneration of ALS model mice - Miyazaki, Kazunori (Nature Publishing Group, 2012)
The exact mechanism of selective motor neuron death in amyotrophic lateral sclerosis (ALS) remains still unclear. In the present study, we performed in vivo capillary imaging, directly measured spinal blood flow (SBF) and glucose metabolism, and analyzed whether if a possible flow–metabolism coupling is disturbed in motor neuron degeneration of ALS model mice. In vivo capillary imaging showed progressive decrease of capillary diameter, capillary density, and red blood cell speed during the disease course. Spinal blood flow was progressively decreased in the anterior gray matter (GM) from presymptomatic stage to 0.80-fold of wild-type (WT) mice, 0.61 at early-symptomatic, and 0.49 at end stage of the disease. Local spinal glucose utilization (LSGU) was transiently increased to 1.19-fold in anterior GM at presymptomatic stage, which in turn progressively decreased to 0.84 and 0.60 at early-symptomatic and end stage of the disease. The LSGU/SBF ratio representing flow–metabolism uncoupling (FMU) preceded the sequential pathological changes in the spinal cord of ALS mice and was preferentially found in the affected region of ALS. The present study suggests that this early and progressive FMU could profoundly involve in the whole disease process as a vascular factor of ALS pathology, and could also be a potential target for therapeutic intervention of ALS.